Bioethical Sensibility and the Role of the Media - Zagorac, Ivana (Array, 2008)
Since its first appearance, bioethics has been developing as both academic field of research and a social movement. The later implements a change in world view as well as emergence of a specific collective sensibility. Defining cultural and social forms of bioethical sensibility requires research of ways and fields of its manifestation. It is a complex interrelationship between media discourse, policy discourses and public perception of issues defined as bioethical that are in focus of our attention. We treat the media as 'cultural indicator' that documents the emerging social representation of bioethical issues. Research into how the media represent bioethical questions is thus a vital part of any agenda concerned with the social aspects of bioethics including its public acceptability and the extent to which the public feel involved in, or is willing to challenge, scientific developments in general. In this sense and within the framework of the „ Founding integrative bioethics“ project special attention is given to the analysis of print media in Croatia. Such an analysis can clearly define phases in the history of bioethical debate in Croatia, what types of arguments, hopes and fears are being mobilized and how this change over the time.